Admission Cardiotocography in High Risk Pregnancies - Thapa, Jwala; Sah, Rajib (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The objective of the study was to evaluate the relationship between admission cardiotocography and fetal outcome among high risk obstetrics patients.Methods: The study was a hospital based observational study of 130 patients, conducted at Paropakar maternity and Women’s Hospital, Kathmandu from January 2014 to June 2014. A 20-minute cardiotocography reading was done in admission room and reading was categorized in 3 groups- reactive, equivocal and ominous. The results were compared to see the relationship between normal and abnormal admission test in terms of color of liquor, mode of delivery, Apgar score at 5 minutes, neonatal resuscitation needed and NICU admission.Results: Result of admission test (AT) was reactive in 95(73.1%), equivocal in 19(14.6%) and ominous in 16(12.3%) which has significant relationship with mode of delivery (p-value=0.003), color of liquor (p-value=0.000), Apgar score at 5 minutes (p-value=0.000) and perinatal outcome (p-value=0.00). Incidences of vaginal deliveries were more common when the test was reactive whereas operative deliveries were more common when the AT was ominous/equivocal.Conclusions: Admission test is simple, cost effective and non-invasive technique for detecting fetal hypoxia and predicting fetal outcome that can serve as a screening tool in triaging fetuses of high-risk patients in developing countries with a heavy workload and limited resources.